Qing Imperial Illustrations of Tributary Peoples (Huang Qing zhigong tu) A Cultural Cartography of Empire - Hostetler, Laura; Wu, Xuemei (Brill, 2022)
Commissioned by the Qianlong emperor in 1751, the Qing Imperial Illustrations of Tributary Peoples (Huang Qing zhigong tu 皇清職貢圖), is a captivating work of art and an ideological statement of universal rule best understood as a cultural cartography of empire. This translation of the ethnographic texts accompanied by a full-color reproduction of Xie Sui's (謝遂) hand-painted scroll helps us to understand the conceptualization of imperial tributary relationships the work embodies as rooted in both dynastic history and the specifics of Qing rule.